OCZYSZCZENIE DUSZ POCZĄTKUJĄCYCH W ŚWIETLE KSIĄŻKI O. RÉGINALDA GARRIGOU-LAGRANGE TRZY OKRESY ŻYCIA WEWNĘTRZNEGO – WSTĘPEM DO ŻYCIA W NIEBIE - Bortkiewicz, Piotr (Civitas et Lex, 2017)
This article presents the way of purification the human soul which allows it to enter a new stage of interior spiritual life. Such a purification requires from the soul great love for God and disdain for itself. It is a very demanding way to make, but such an effort is worth being made, as it guarantees the experience of God and His love.